Nutrition as a basic need: A new method for utility-consistent and nutritionally adequate food poverty lines - Mahrt, Kristi; Herforth, Anna W.; Robinson, Sherman; Arndt, Channing; Headey, Derek D. (International Food Policy Research Institute, 2022)
In most countries and globally, malnutrition rates exceed poverty rates. The World Bank estimates that about 9 percent (689 million) of the global population is poor, yet an estimated 25 percent (2 billion people) suffer from micronutrient deficiencies. Such a discrepancy begs the question: Do standard poverty metrics poorly reflect nutritional needs? The most prevalent methodology for measuring poverty in low- and middle-income countries – the cost of basic needs approach – estimates food baskets that satisfy a dietary energy standard while reflecting consumption patterns of poor households. However, poor households typically consume monotonous diets characterized by large quantities of calorically cheap staple foods that are poor sources of nutrients. This reality creates a circular logic whereby the cost of basic nutritional needs is estimated from populations who are consuming nutritionally inadequate diets. We argue that a healthy diet is a basic need and that the standard used to calculate cost of basic needs food poverty lines should be expanded to satisfy nutritional dietary recommendations, while continuing to reflect context-specific dietary patterns. We develop an approach to estimate food poverty lines that satisfies the food group proportionality associated with healthy diet recommendations while also adhering to observed within-food group consumption patterns of poor households. Furthermore, we address the limitation of estimating a single national food basket – which fails to capture variation in local consumption patterns driven by preferences, availability, and relative prices – by estimating utility-consistent regional poverty lines. We demonstrate the approach using data from Myanmar. Energy-based poverty lines significantly underestimate the cost of acquiring a healthy diet, are severely deficient in multiple micronutrients, and therefore result in a drastic underestimate of the rate of poverty based on a healthy diet standard. The resulting higher cost of basic needs also has important implications for inclusive economic growth strategies and nutrition-sensitive food policies and social protection.